2020
DOI: 10.4209/aaqr.2020.03.0097
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Forecasting Using Artificial and Wavelet Neural Networks with Meteorological Conditions

Abstract: Air quality forecasting is a significant method of protecting public health because it provides early warning of harmful air pollutants. In this study, we used correlation analysis and artificial neural networks (ANNs; including wavelet ANNs [WANNs]) to identify the linear and nonlinear associations, respectively, between the air pollution index (API) and meteorological variables in Xi'an and Lanzhou. Evaluating twelve algorithms and nineteen network topologies for the ANN and WANN models, we discovered that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Artificial intelligence (AI) has been proven of their feasibility in capturing nonlinear relationships. Artificial intelligence has been widely used in many fields (Cassimon et al 2020;Guo et al 2020;He et al 2014), and AI can quickly diagnose COVID-19 (Zhang et al 2020). To overcome limitations of the epidemiological model, we develop artificial intelligence (AI) for real-time predicting of the new confirmed cases of COVID-19 all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) has been proven of their feasibility in capturing nonlinear relationships. Artificial intelligence has been widely used in many fields (Cassimon et al 2020;Guo et al 2020;He et al 2014), and AI can quickly diagnose COVID-19 (Zhang et al 2020). To overcome limitations of the epidemiological model, we develop artificial intelligence (AI) for real-time predicting of the new confirmed cases of COVID-19 all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Ye’s analysis of Fairbanks confirmed that air temperature and AQI were positively correlated, while visibility was negatively correlated with AQI 28 . Guo studied the correlation between meteorological factors and AQI and also verified that there was a positive correlation between temperature and AQI 29 . These are consistent with the correlation analysis results obtained in this paper.…”
Section: Resultsmentioning
confidence: 93%
“…An information-driven way to deal with displaying COVID-19 has likewise arisen, in which measurable and machine learning models are utilized for gauging cases, hospitalizations, passings, and effects of social separating [ 26 , 27 ]. Considering machine learning approaches, forecasting by using artificial and wavelet neural networks with meteorological conditions has been studied by Guo et al [ 28 ]. Guo and He [ 29 ] predicted confirmed death cases together with confirmed global COVID-19 confirmed cases utilizing artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%